Can CC16 Levels in Serum and TGF-?1, Caspase-3, Caspase- 8, and Caspase-9 Levels in Bronchoalveolar Lavage Fluid Be Early Markers in Premature Patients with Bronchopulmonary Dysplasia? - Durukan, Mehtap; Aldas, Sefika; Canacankatan, Necmiye; Taskın, Erdal; Aygun, A. Denizmen (My University, 2024)
Objective: Advances in neonatal intensive care have increased the survival rate of premature infants, but the incidence of bronchopulmonary dysplasia (BPD) has also risen. Early markers for BPD are still unclear. This study investigates the relationship between BPD development and levels of clara cell secretory protein 16 (CC16), Transforming growth factor-?1 (TGF-?1), and caspase-3, caspase-8 and caspase-9. Materials and Methods: On days 1, 3, 14, and 28 of life, bronchoalveolar lavage fluid and serum samples were obtained from infants born before 32 weeks gestation and intubated for respiratory distress. 41 cases, including 21 neonates with BPD and 20 without, were included. Results: CC16 levels were consistently higher in the BPD group, peaking on day 3, with significant differences on days 14 and 28 (p<0.05). TGF-?1 was highest on day 1 in the BPD group, decreasing by day 3, but remained higher than in controls (p<0.05). Caspase levels were similar on day 1 but significantly higher in the BPD group on day 3. On day 14, all caspase levels decreased, with caspase-3 continuing to decrease on day 28 while caspase-8 and caspase-9 rose again. Increased uncontrolled apoptosis, particularly through the extrinsic pathway, was linked to BPD development. Conclusion: CC16, TGF-?1, and caspases are potential early markers for BPD and could guide new treatment modalities.
Keywords: TGF-?1; Bronchopulmonary dysplasia; caspases; CC16